Viability Lactic Acid Bacteria of Yogurt Powder With Carrageenan Addition - Anugrah Tamam Basroni; Ahmad Ni'matullah Al-Baarri; Anang Mohamad Legowo (Journal of Applied Food Technology, 2018)
This research aimed to analyze the viability of lactic acid bacteria in carrageenan fortified yogurt powder. This research was done in Laboratory of Food Chemistry and Nutrition Faculty of Animal and Agriculture and Laboratory of Integrated Diponegoro University. Yogurt was made using pasteurized fresh milk and inoculated with Lactobacillus bulgaricus and Streptococcus thermophillus. The incubation was set to 6 hour and followed drying in vacuum oven. Carrageenan 0.5% (w/v) was mixed prior to the drying. The all treatment was repeated 4 times. The viability of lactic acid bacteria in powdered yogurt was analysed during 10 days. The results of this research showed that carrageenan addition provide no noticeable effect to the viability in powdered yogurt during the ten days storage. The conclusion of this research was carrageenan may be used in powdered yogurt without provide any affect in the viability of lactic acid bacteria.